Endocannabinoid Function in Hippocampal Synaptic Plasticity and Spatial Working Memory - Blaskovits, Farriss (Université d'Ottawa / University of Ottawa, 2013)
Cannabis has been used medicinally for millennia, but the cannabinoid (CB) field exploded with the identification of its endogenous receptors and endocannabinoids (eCBs). In vitro experimentation established that eCBs alter synaptic plasticity at presynaptic nerve terminals; however, the characterization of the eCB system (ECS) in vivo remains incomplete. This study aimed to determine the mechanism of in vivo eCB-mediated hippocampal synaptic plasticity and to analyze the effects this plasticity had on spatial working memory (SWM). With in vivo recordings of field excitatory postsynaptic potentials (fEPSPs) in anesthetized mice and rats as well as pharmacological manipulation of the ECS and glutamate receptor antagonism, it was found that eCBs, both anandamide (AEA) and 2-arachnidonyl glycerol (2-AG), caused LTD at hippocampal CA3-CA1 synapses. Induction of eCB-LTD occurs via a sequential activation of cannabinoid type-1 receptor (CB1R) and NR2B-containing NMDA receptor (NR2BR) and is expressed through the endocytosis of AMPA receptors (AMPARs). Increased eCB tone also caused an impairment of SWM for over 24 hours in the Delayed Non-Match-To-Sample (DNMTS) T-maze. This study provides the first evidence that an acute administration of eCB degradative enzyme inhibitors not only produces an in vivo LTD at hippocampal CA3-CA1 synapses that requires CB1R, NR2BR, and AMPAR, but also impairs SWM, a phenomenon also caused by an acute injection of exogenous CBs.
Keywords: Endocannabinoids; hippocampus; spatial working memory; synaptic plasticity